2018
DOI: 10.1002/adfm.201807345
|View full text |Cite
|
Sign up to set email alerts
|

Light Emitting Diodes Based on Inorganic Composite Halide Perovskites

Abstract: CsPbBr 3 is a promising type of light-emitting halide perovskite with inorganic composition and desirable thermal stability. The luminescence efficiency of pristine CsPbBr 3 thin films, however, appeared to be limited. In this work, we have demonstrated light emitting diodes based on CsPbBr 3 |Cs 4 PbBr 6 composites. Both quantum efficiency and emission brightness have been improved significantly compared with similar devices constructed using pure CsPbBr 3 . The high brightness can be attributed to the enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 42 publications
1
76
0
Order By: Relevance
“…[6] In addition, all-inorganic low-dimensional nanomaterials based on 3D CsPbX 3 structures have exhibited relatively high photoluminescence quantum yields (PLQYs). [7] In contrast, at the molecular level, all-inorganic low-dimensional metal halides,w hich generally have better thermal stability and are favorable for practical applications, [8] suffer from low PLQYs. [5b-d] The necessity of developing environmentally sustainable allinorganic low-dimensional metal halides with excellent optoelectronic properties naturally drove our attention to transition metals.Among them, copper is of great interest because of its abundance,l ow cost, and low environmental impact.…”
Section: Organic-inorganicmetalhalidesemiconductorshaveshownmentioning
confidence: 99%
“…[6] In addition, all-inorganic low-dimensional nanomaterials based on 3D CsPbX 3 structures have exhibited relatively high photoluminescence quantum yields (PLQYs). [7] In contrast, at the molecular level, all-inorganic low-dimensional metal halides,w hich generally have better thermal stability and are favorable for practical applications, [8] suffer from low PLQYs. [5b-d] The necessity of developing environmentally sustainable allinorganic low-dimensional metal halides with excellent optoelectronic properties naturally drove our attention to transition metals.Among them, copper is of great interest because of its abundance,l ow cost, and low environmental impact.…”
Section: Organic-inorganicmetalhalidesemiconductorshaveshownmentioning
confidence: 99%
“…As a frequently used method in the fabrication of perovskite films, chemical vapor deposition (Figure 15a) was also employed in the synthesis of the dual-phase inorganic CsPbX 3 / Cs 4 PbX 6 perovskite film. [172][173][174][175][176][177] During the preparation process, it was found that the CsBr/PbBr 2 ratio was a very significant parameter in determining the PL emission intensity. [172] When the ratio was 44:16.5, the sample exhibited the highest PL efficiency (Figure 15b,d,e).…”
Section: Bulk/filmmentioning
confidence: 99%
“…However, its performance was unsatisfactory. Recently, the performance of LEDs based on the CsPbBr 3 /Cs 4 PbBr 6 composite was improved by modifying active layers through thermal evaporation [117,175] and organic molecule addition. [206,207] When the CsPbBr 3 /Cs 4 PbBr 6 composite film was fabricated via thermal evaporation, the corresponding LEDs showed a green electroluminescence with a maximum luminance of 55 000 cd m −2 and an EQE of 2.5%.…”
Section: Ledsmentioning
confidence: 99%
“…The PCE of perovskite solar cells produced by VBD has reached 20%, close to solution‐processed devices. However, perovskite LEDs produced by VBD were less studied, and device performance lagged significantly behind …”
Section: Introductionmentioning
confidence: 99%